2022
DOI: 10.1007/s40866-022-00125-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary Frequency Regulation Based on Deloaded Control, ANN, and 3D-Fuzzy Logic Controller for Hybrid Autonomous Microgrid

Abstract: This study proposes an original approach to improve the Primary Frequency Regulation (PFR) of an Autonomous Microgrid (A-μG). The Wind Turbine Generator (WTG) is considered to be a principal resource. Due to the wind variability and intermittency, Diesel Generator (DG) is incorporated to meet the load peak. However, to reduce the system maintenance and fuel consumption and to increase the microgrid efficiency, Battery Energy Storage System (BESS) is added. Hence, to meet the load demand, the A-μG relies on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…By regulating the ARS, the WT is able to generate an optimal mechanical power, P m , as given in [13,14]:…”
Section: Wind Turbine-mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…By regulating the ARS, the WT is able to generate an optimal mechanical power, P m , as given in [13,14]:…”
Section: Wind Turbine-mathematical Modelingmentioning
confidence: 99%
“…According to [13,21], for each ARS, the reference of the de-loaded WTG-power, P ref , is calculated as indicated in (11):…”
Section: De-loaded-lvrt Techniquementioning
confidence: 99%
“…Future plans involve experimental validation and integrating energy optimization into the system. The study [9] suggested a new way to improve a small self-sufficient power grid using wind and diesel generators, along with batteries for efficiency. An intelligent energy management system (IEMS) was made in two steps: first, using extra energy when wind is low or demand is high, and second, using smart controls to boost performance.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a controller with a linear model operates in a linear range, but due to the capabilities of ANN in solving problems with high mathematical complexity and the high power of these networks in estimating functions, designers are encouraged to use these networks in the design of self-tuning controllers to control nonlinear processes 23 . In [24][25][26][27] , a PI-controller with a hybrid ANN form is used as a direct adaptive controller to control the microgrid frequency, in which PSO and fuzzy algorithms are used to optimize ANN coefficients and their rapid training.…”
mentioning
confidence: 99%